The Insecticidal Effects of Nogos and Sumicidin Against Eggs and Larvae of The Mosquito Culex pipiens L.(Diptera: Culicidae) - Al-Chalabi, B. M; Mones, A. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The two i nsecticides Nogos and Sumicidin were tested for their activity against larvae and eggs of Culex pipiens under laboratory conditi on. Third instar larvae were exposed for 24, 48 and 72. hrs to five concentrations each insecticide test: 0.0005, 0.005, 0.05, 0.5 and 1.0 ppm. The same concentrations were used to test the eggs hatching. The results showed that Nogos was more effective than Sumicidin. This insecticide (Nogos) demonstrated larval mortal ities (94%) after 24 brs and (98%) aft.er 72 hrs at 1 .0 ppm while with Sumicidin, the larval mm1a lities were (53%) and (78%) after 24 hrs and 72 hrs respectively at the same concentrati on. The exposure of deposited eggs of C. pipiens lO 0.0005- 1.0 ppm of both insecticides revealed no noticeable ovicidal effects with Sumicidin, but with Nogos the (% hatching) was 65.66 atl.O ppm.